L’idéologie desarrollista dans 2666 de Roberto Bolaño - Iris Cotteaux (Cahiers des Amériques Latines)
If the substantive “development” is synonymous with “growth”, “expansion”, or “progress”, can it describe Latin America, and particularly postmodern Chile or postmodern Mexico? Numerous official speeches resort to this term, but what is the situation with unofficial speeches, among which are literary speeches?In order to go deeper into and to target the question, in this work, we will wonder which views express a Chilean novelist internationally known, Roberto Bolaño (1953-2003), on Latin-American development, through his masterpiece, the novel 2666, published posthumously in 2004. To portray a drifting Latin America at different levels, the writer opts for an aesthetic which meets the codes of literary postmodernity, as the Egyptian Ihab Hassan conceive it in The Postmodern Turn: Essays in Postmodern Theory and Culture (1987), that is to say based on formal fragmentarity, on character’s disintegration, on a pessimistic tone and on parody. The analysis of the processes of this aesthetics of dislocation will allow us to shade the official speech which tends to present Latin-American countries as “emerging”. To finish, we will wonder about intentions of such pessimistic literary speech about development. Indeed, Bolaño doesn’t content himself with revealing nor denouncing creating a counter-speech, but he aims at the same time at leading his reader, through humour and detective diction, to awakening.